2019
DOI: 10.1112/plms.12306
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the analytic λ‐invariant over a solvable extension

Abstract: Fix an odd prime p, and suppose that D∞ = n Dn is a solvable p-adic Lie extension of the rationals, such that Gal(Dn/Q) ∼ = (Z/p n Z) g (Z/p n Z) × for some g > 0 and n n. In particular, this situation covers the well-known cases where (i) D∞ = Q(μp∞ , Δ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The aim here, and in the companion work [6], is to provide a positive answer. In fact we only discuss = alg in this paper; the complementary case = an is more difficult and technical, and so it is dealt with in op.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The aim here, and in the companion work [6], is to provide a positive answer. In fact we only discuss = alg in this paper; the complementary case = an is more difficult and technical, and so it is dealt with in op.…”
Section: Introductionmentioning
confidence: 94%
“…Before proving the four main theorems from Section 1•1, we first briefly recall the important properties of the Hecke algebra, T (ρ), which controls the Hida family. The principal reference is of course [11], although [2,6] are maybe shorter to read.…”
Section: Control Theory For the Algebraic λ-Invariantmentioning
confidence: 99%
“…If µ (j) I,II ∈ Z ∪ {+∞} denotes the minimum of the µ-invariants for L p (f ⊗ g (I) , ω j ) and L p (f ⊗ g (II) , ω j ), then by Theorem 3.3 one has −µ Σ , ω j )) = λ(L p (f ⊗ g ( ) , ω j )) + e ( ) l (ω j ). 5 This containment is also true for the missing characters, which can be seen by exploiting the p-adic density of finite order characters χ with χ F × p = ω j inside the parameter space 1 + pZp. g , because here E l (f ⊗ g (I) , ω j ) ≡ E l (f ⊗ g (II) , ω j ) mod ep•ν 2 .…”
Section: Remarksmentioning
confidence: 97%
“…Emerton, Pollack and Weston [9] later generalised this construction to allow f to vary within a Hida family, and showed that the λ-invariant was stable along the branches of a certain Hecke algebra, T Σ (ρ), parameterising the deformation. Recently the theory has been extended to cover anticyclotomic λ-invariants in the work of Castella, Kim and Longo [1], and also to treat non-commutative p-adic Lie extensions (with a meta-abelian structure) by the first-named author in [5,6]. Further generalisations of Vatsal's original ideas can be found in [2,7,8,19,22].…”
Section: Question How Do the Analytic And Algebraic λ-Invariants Appearing In The Main Conjecture Vary As We Switch Between Two P ν -Congmentioning
confidence: 99%